Regulation commissions in Colombian law. Anatomy of a government agency - Pimiento Echeverri, Julián Andrés (2016)
Economic regulation as an administrative activity has become one of the quintessential subjects in modern Colombian administrative law. Despite the fact that Colombian law uses a fairly restrictive, organic, approach to economic regulation, few studies have analysed that connection between economic regulation and Government agencies. Without taking sides with that restrictive approach, this article tries to show the inconsistencies and difficulties to regulate properly in Colombian law, because of that connection between that administrative activity and those special agencies: the regulation commissions.